The probabilities of psychiatric hospitalization of mental health clinic patients - Reis, Leonardo Naves dos; Simplicio, Julio Cesar Ribeiro; Gherardi-Donato, Edilaine Cristina da Silva; Zanetti, Ana Carolina Guidorizzi (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2015)
The objective of this study is to evaluate the factors of prediction (diagnostic and socio-demographic characteristics) regarding psychiatric outpatient mental health among users. The study was conducted from secondary data, extracted from the charts and analyzed through logistic regression, to obtain the prediction equation of probability of psychiatric hospitalization. The diagnoses that showed statistical significance (p < 0.05) were bipolar affective disorder, schizophrenia, anxious disorders and depression, and the first two showed a high magnitude association with the need of hospitalization. The age was inversely proportional to the need of hospitalization. The results found may stimulate specific actions and the psychiatric prevention of younger patients with schizophrenia and bipolar affective disorder.